Rivalry intervention in civil conflicts: Afghanistan (India-Pakistan), Angola (USSR-USA), and Lebanon (Israel-Syria) - Mitton, John Logan (Canadian foreign policy journal, 2017)
This article focuses on international intervention into civil conflict by international rivals; that is, the phenomenon of two states, locked in a long-term and ongoing acrimonious relationship, intervening on opposing sides of a civil conflict occurring in a third party. International rivalry, it is argued, is an ongoing strategic relationship in which the push of the past and the pull of the future engenders balancing behaviour vis à vis third-party civil conflicts. This argument is evaluated in the context of three cases of rivalry intervention: Afghanistan (India-Pakistan); Angola (USSR-USA); and Lebanon (Israel-Syria). While rivalry dynamics are not the sole motivator for intervention in each case, rivals do worry about the future, and as a result consider and assess the implications of their opponents' involvement in a civil conflict in the context of potential future confrontation.